Addressing Barriers to WIC Participation During COVID-19: A Qualitative Examination of California WIC Participants and Local Agency Directors. (14th June 2022) - Chaney, Alana; Au, Lauren; Anderson, Christopher; Hecht, Christina; Martinez, Catherine; Ritchie, Lorrene; Tsai, Marisa; Vital, Nicole; Whaley, Shannon
Abstract: Objectives: Economic impacts of COVID-19 have intensified the burden of food insecurity amongst low-income minority populations, especially women and children. This study aimed to understand the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) participant and local agency director experiences with the adoption of USDA federal waivers, designed to overcome operational barriers during the COVID-19 pandemic in 3 regions in California. Methods: A qualitative cross-sectional study included structured phone interviews (June 2020-March 2021) in Spanish or English of 182 California WIC participants' experience and satisfaction with remote interactions, enrollment or recertification in WIC, and shopping for WIC foods. Twenty-two local agency directors were interviewed on how operational challenges were overcome, and preferences on the continuation of specific waivers post-pandemic. The study utilized integrated approach comprised of deductive framework and inductive identification to organize interview responses and identify themes for statistical analysis. Results: Most WIC participant respondents (69%) were on WIC prior to the pandemic; 39% enrolled in WIC in March 2020 or later. Most participants were moderately (41%) or very (40%) concerned about the pandemic with more than a quarter (29%) experiencing less income due to COVID-19 challenges. A third (30%) reported challenges shopping for WIC foods at the start of the pandemic with the most common being milk (64%), eggs (33%), and fresh fruit (33%). Despite most participants (63%) reporting household food insecurity, 70% reported how easy and quick it was enrolling in WIC services. Most WIC agency directors (59%) reported offering only virtual services. Nearly all (95%) of agency directors wanted to continue the option to certify participants remotely, and all directors desired to continue issuing food benefits remotely, both practices enabled by federal waivers. Directors reported that WIC clinics were successfully able to pivot to remote operations because of the USDA federal waivers. Conclusions: WIC may attract and retain most families by incorporating a hybrid approach including both on-site services and remote options. Funding Sources: The David and Lucile Packard Foundation.